(untitled) (Zaporizhzhia Historical Review, 2021)
This article is dedicated to the problem of economic literature translation. This problem has become topical nowadays because of the international economic contacts development. The following problems are highlighted in this article: types of economic texts, which should be identified before starting translation, the main problems of economics texts translation and specificity of neologisms in economics literature.